The influence of blade parameters on the performance of propeller pico hydro turbine for rural electrification - Musa, Masjuri (2018)
Propeller Pico hydro turbine is one of the hydro turbine schemes which is capable to produce power output up to 5 kW. This stand-alone hydro system uses the run-off-river method with the application of penstocks to deliver the necessary water flow rate to the turbine system. In Malaysia, most of the rural sites offer significant sources of river flows with annual average 100 L/s to distribute power without the need for grid. In order to ensure the propeller hydro turbine can perform as required, both head and water flow rate are the two crucial parameters that must be taken into consideration. Since propeller Pico hydro turbine is more suitable to operate under low head, the water flow rate should be high enough to ensure power output generated by the hydro turbine can reach its maximum output. However, during dry season, the level of the river water will become low and even the stream flow of the water can become slow and unsteady. This phenomenon affects the overall performance of the Pico hydro turbine. The slow flow causes the rotational speed of the blades to become slower and indirectly the generator of the propeller hydro turbine produces very little power output. Therefore, the investigation on the influence of blade parameter configurations such as the hub-to-tip ratio, number of blades, and blade angles on the performance of the propeller hydro turbine were done under these stipulated condition. In addition, the straight flat profile with constant thickness and blade width are other blade criteria which are being focused. In this particular case, in which both head and flow rate are in low conditions, the values were fixed at 2.3 m height and 13 L/s water flow rate. At the initial stage, before proceeding to the actual experiments, the implementation of CFD simulation analysis was conducted on the mentioned blade design parameter configurations to serve as a design tool and reference for a better understanding of the experimental findings. Next, a Pico hydro test rig was designed and developed for the experimental purpose. After confirmation was made with the actual experiments, all related data were compiled together to identify the influence of combination related to blade parameters. Comparison on the Cost of Energy (CoE) was conducted between the hydro turbine and the standalone fuelled generator, where hydro turbine provided better amount of CoE which was 3.77 RM/kWh. From the Life Cycle Cost Analysis (LCCA), hydro turbine provided better Return of Investment (RoI) and Payback Period (PP) compared to standalone generator which is 44% and 5 years respectively. The final results showed the maximum electrical power output generated by the hydro turbine was 17 W, while the efficiency was 45%. In conclusion, the hub-to-tip ratio contributed the most on the performance of the hydro turbine, followed by the number of blades and lastly the blade angles. The best combination of blade parameter configurations is 0.4 for the hub-to-tip ratio, with three blades at 70° angle.